Widely targeted metabolomics analysis reveals the mechanism of quality improvement of flue-cured tobacco - Meng, Lin; Song, Wenjing; Chen, Shuaiwei; Hu, Fengqin; Pang, Bingwen; Cheng, Junjie; He, Bing; Sun, Fushan (Frontiers in Plant Science, 2022)
Flue-curing of top leaves with stems is a widely applied curing technology. Owing to the presence of stems, the quality of flue-cured leaves was significantly improved. However, the contribution of stems to flue-cured leaves is still unknown. In this study, the differences in physicochemical properties and metabolomics data between separated leaves (stem(-)) and leaves with stems (stem(+)) were investigated. The metabolic profiling of stem(+) was significantly different from that of stem(-), with phytohormone indole-3-acetic acid (IAA) being one of the most differential metabolites. The presence of stems reduced the rate of water loss in leaves, which led to less ROS accumulation, higher antioxidant enzyme activities and a lower level of membrane lipid peroxidation in stem(+) than in stem(-). The presence of stems also helped maintain the cellular membrane integrity of leaf cells by preventing the accumulation of IAA in leaf cells. Better cellular membrane integrity during flue-curing means a lower risk of leaf browning. In addition, stem(+) had a lower starch content than stem(-) because of a higher level of amylase activity. In summary, these results indicated that the presence of stems caused metabolism changes in leaves, prevented flue-cured leaves from browning and enhanced starch degradation in leaves during flue-curing.